Mobile-assisted language learning (MALL) research trends and patterns through bibliometric analysis: Empowering language learners through ubiquitous educational technologies. (November 2022) - Karakaya, Kadir; Bozkurt, Aras
Abstract: Mobile devices and technologies have proliferated extensively and become an integral part of life and learning. Mobile-assisted language learning (MALL) has progressed as an emerging area of research corresponding to recent advances in mobile technologies and the proliferation of smartphones and tablet computers. Accordingly, this study examined MALL research between 2008 and 2020 through a bibliometric analysis using social network analysis (SNA) and text mining techniques. The SNA and text mining analysis suggest five broad research themes: (1) self-regulated language learning by defining one's own learning objectives, (2) providing learner agency and motivation by empowering autonomy, (3) personalizing learning through artificial intelligence (AI)-supported mobile learning (m-learning), (4) MALL for learning in the wild, and (5) MALL to support higher education. The findings show that while MALL research has been considerably operationalized around linguistic factors, nonlinguistic factors relating to learners' interactions with mobile devices or applications have been largely overlooked. It was found that MALL scholarship has recently tended to incorporate the use of mobile devices in informal learning contexts and outside the classroom due to the flexibility and anytime anywhere functionality of m-learning. The study concludes with several suggestions and highlights the areas that need more attention in MALL research.